2021
DOI: 10.3389/fcell.2021.748631
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical Models of Metastasis in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a hostile solid malignancy coupled with an extremely high mortality rate. Metastatic disease is already found in most patients at the time of diagnosis, resulting in a 5-year survival rate below 5%. Improved comprehension of the mechanisms leading to metastasis is pivotal for the development of new targeted therapies. A key field to be improved are modeling strategies applied in assessing cancer progression, since traditional platforms fail in recapitulating the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 224 publications
0
24
0
1
Order By: Relevance
“…Another major challenge in PDAC treatment is the very high metastatic potential, especially in the lungs and liver. It is also confirmed that metastasis occurs very early in cancer progression, where no specific symptoms of the disease are observed [ 13 ]. This is also a major problem because PDAC diagnosed at an early stage of progression can be fully treated, as mentioned above.…”
Section: Introductionmentioning
confidence: 83%
“…Another major challenge in PDAC treatment is the very high metastatic potential, especially in the lungs and liver. It is also confirmed that metastasis occurs very early in cancer progression, where no specific symptoms of the disease are observed [ 13 ]. This is also a major problem because PDAC diagnosed at an early stage of progression can be fully treated, as mentioned above.…”
Section: Introductionmentioning
confidence: 83%
“…As expected, the tumors that developed were very dense and had defined capsules visually apparent as a thick, glossy layer surrounding each tumor. These subcutaneous tumors were not expected to metastasize ( Miquel et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Metastasis is characterized by cancer cells invading the basement membrane into the adjacent matrix, then invading and surviving into the circulatory system (including blood and lymphatic tissue), and extravasation to distant tissues. A core step in the process of cancer metastasis is the acquisition of migratory and aggressive phenotypes ( 37 ). In 9 types of tumors, the abnormal down-regulation of miR-1301 will affect p53, WNT, STAT3, and other signaling pathways, which can promote tumor cell migration and invasion.…”
Section: The Aberrant Expression Of Mir-1301 In Cancermentioning
confidence: 99%